On the Problem of Determining the Genre of Gregor von Rezzori’s “The Snows of Yesteryear” (Flowers in the Snow) - Basniak, Tetiana (Pitannâ lìteraturoznavstva, 2013)
The body of the article goes on to disclose an autobiographical essay of the major author in the German-speaking area, Gregor von Rezzori’ “Flowers in the Snow” in terms of its genre specific ambiguity. After writing hypothetical autobiographies endlessly, Rezzori dare write an apparently autobiographical novel. Critiques considered him to reach the top of the most-exciting-authors list of the German literature. However, researchers have not determined Rezzori’s Blumen im Schnee so far as an undoubtedly autobiographical book as the genre of classic autobiography. The purpose of the given academic research is to define clear boundaries of its genre model. The problem of Defining the genre becomes far more complex because of representation of ironic pathos. Ironic charades ferment and disguise its real genre format. The author’s astounding ability to arrange his thoughts with insight and poetry enables him to do so while remaining a few paces away from the threshold of historical chronicles. The Outlined perspective is highlighted by the methodological framework of such poetological branches as time space theory and genre forms, structural and semantic hermeneutics-receptive areas of a present day history of literature, and the works of foreign adepts of Rezzori’s works. Taking into account the receptive capacity of the work, it can be determined in the sense of connotations of its genre parameters. The findings lie in the idea that Rezzori’s conventional autobiographical novel appears equally as education novel and might be considered as a synthesis of the two genres subtypes. Firstly, individuality establishing occurs in the biographical time, passing through the unique individual stages. Secondly, a personality self-making is portrayed in close connection with the historical development, it is a historical reality. Noteworthy, the text balancing on the verge of several varieties of genre should be considered as the author’s attempt to find a balance, so its composing is a main obvious “auto-therapeutic” purpose.